Cost-effectiveness analysis of flucytosine as induction therapy in the treatment of cryptococcal meningitis in HIV-infected adults in South Africa - Jacqui Miot; Trudy Leong; Simbarashe Takuva; Andrew Parrish; Halima Dawood (BMC, 2021)
Abstract Background Cryptococcal meningitis in HIV-infected patients in sub-Saharan Africa accounts for three-quarters of the global cases and 135,000 deaths per annum. Current treatment includes the use of fluconazole and amphotericin B. Recent evidence has shown that the synergistic use of flucytosine improves efficacy and reduces toxicity, however affordability and availability has hampered access to flucytosine in many countries. This study investigated the evidence and cost implications of introducing flucytosine as induction therapy for cryptococcal meningitis in HIV-infected adults in South Africa. Methods A decision analytic cost-effectiveness and cost impact model was developed based on survival estimates from the ACTA trial and local costs for flucytosine as induction therapy in HIV-infected adults with cryptococcal meningitis in a public sector setting in South Africa. The model considered five treatment arms: (a) standard of care; 2-week course amphotericin B/fluconazole (2wk AmBd/Flu), (b) 2-week course amphotericin B/flucytosine (2wk AmBd/5FC), (c) short course; 1-week course amphotericin B/flucytosine (1wk AmBd/5FC) (d) oral course; 2-week oral fluconazole/flucytosine (oral) and e) 1-week course amphotericin B/fluconazole (1wk AmBd/Flu). A sensitivity analysis was conducted on key variables. Results The highest total treatment costs are in the 2-week AmBd/5FC arm followed by the 2-week oral regimen, the 1-week AmBd/5FC, then standard of care with the lowest cost in the 1-week AmBd/Flu arm. Compared to the lowest cost option the 1-week flucytosine course is most cost-effective at USD119/QALY. The cost impact analysis shows that the 1-week flucytosine course has an incremental cost of just over USD293 per patient per year compared to what is currently spent on standard of care. Sensitivity analyses suggest that the model is most sensitive to life expectancy and hospital costs, particularly infusion costs and length of stay. Conclusions The addition of flucytosine as induction therapy for the treatment of cryptococcal meningitis in patients infected with HIV is cost-effective when it is used as a 1-week AmBd/5FC regimen. Savings could be achieved with early discharge of patients as well as a reduction in the price of flucytosine.